Runoff regulation and nitrogen and phosphorus removal performance of a bioretention substrate with HDTMA-modified zeolite - Qin, Yifeng; Chen, Mingshen; Liu, Shuchang; Fang, Yunqing; Li, Xudong; Qiu, Jiangpin (Frontiers in Environmental Science, 2023)
As a commonly used material in bioretention substrate, natural zeolite (NZ) provides decent adsorption capacity for cation pollutants and heavy metals, but limited ability to removal anion pollutants. Hexadecyl trimethyl ammonium bromide (HDTMA) modified zeolite (MZ) were used as bioretention substrate material. The performance of the media including runoff reduction, nitrate nitrogen (NO3–N) removal, ammonium nitrogen (NH4+-N) removal, and total phosphorus (TP) removal were assessed by column experiment. The effect of different level of modification, ratio of zeolite in substrate, and rainfall intensity on media performance were investigated. Results indicate that HDTMA modified zeolite significantly improves the NO3–N (up to 38.2 times of NZ) and TP (up to17.5 times of NZ) removal rate of media, and slightly increases the NH4+-N (up to 1.5 times of NZ) purification performance of substrate. Compared with media with NZ, decline on both runoff volume reduction (maximum decline up to 32.9%) and flow rate reduction (maximum decline up to 29.9%) of media with MZ were observed. Based on multiple regression analysis, quantitative relationship models between influencing factors and response variables were established (R2>0.793), level of effect of influencing factors on response variables were investigated, as well as the interactions between influencing factors were explored. Main effect analysis found that the degree of modification affects NO3–N and TP removal rate of substrate the most, and when amount of HDTMA molecules loaded on zeolite surface exceeds 0.09meq/g, the modification can no longer improve NO3–N removal efficiency.